Aproximación al estudio de los sistemas de recuperación de imágenes “CBIR” desde el ámbito de la documentación - Pérez Álvarez, Sara (Documentación de las Ciencias de la Información, 2006)
CBIR systems were put forward in the early 1990’s in areas related to automated vision and image process. Despite the possibilities of CBIR in overcoming the traditional text-based paradigm of image analysis and retrieval, research on these systems carried out by Information Scientists is scarce. The author hence reflects on the potential contribution of Information Science to the study of these systems.
Keywords: Image Retrieval Systems; CBIR; Image Documentation